A new approach to characterising the porosity of particle modified electrodes: Potential step chronoamperometry and the diffusion indicator. (December 2021) - Yang, Minjun; Batchelor-McAuley, Christopher; Kätelhön, Enno; Compton, Richard G.
Highlights: Diffusion indicator is used to characterise electrodes modified with spherical blocks. Bottle-neck in diffusion is revealed by the diffusion indicator. The intertwined thin-layer and semi-infinite diffusion can be identified. Abstract: A new approach is reported for the characterisation of diffusional transport within porous layers used to modify the surfaces of electrodes, as is commonly deployed in the design of new amperometric sensors and for developing electro-catalytic electrodes. In particular we show that measurement and analysis of the current–time transients associated with a potential step at the electrode such that an electroactive analyte is oxidised or reduced at the electrode surface provides much information about the porosity and size of the layer and the constituent particles and highlights the intertwined thin-layer and semi-infinite diffusion as a function of the timescale of electrolysis. The work simulates the chronoamperometry response of electrodes modified with between 0 and 10 layers of spheres acting as partial blocks reducing but not fully preventing diffusional access to the electrode. By analysing the flux-time transient, the diffusion indicator, α, [Le et al ., J. Electroanal. Chem, 2019, 855, 113, 602] is shown to be able to reveal bottlenecks to the transport caused by the packing of the spherical blocks and to indicate the timescale at which this is observed which is intermediate to the Cottrellian responses seen at very short or very long times. Further, the indicator provides the point in the flux-time transient at which diffusion is no longer confined to within the porous layer, thus providing a method to estimate the thickness of the porous layer. Graphical abstract: Image, graphical abstract